Enterococcus species distribution among human and animal hosts using multiplex PCR - Layton, B.A; Walters, S.P; Lam, L.H; Boehm, A.B (Journal of applied microbiology, 2010)
This study evaluated the use of Enterococcus species differentiation as a tool for microbial source tracking (MST) in recreational waters. Avian, mammalian and human faecal samples were screened for the occurrence of Enterococcus avium, Enterococcus casseliflavus, Enterococcus durans, Enterococcus gallinarum, Enterococcus faecium, Enterococcus faecalis, Enterococcus hirae and Enterococcus saccharolyticus using multiplex PCR. Host-specific patterns of Enterococcus species presence were observed only when data for multiple Enterococcus species were considered in aggregate. The results suggest that no single Enterococcus species is a reliable indicator of the host faecal source. However, Enterococcus species composite 'fingerprints' may offer auxiliary evidence for bacterial source identification. This study presents novel information on the enterococci species assemblages present in avian and mammalian hosts proximate to the nearshore ocean. These data will aid the development of appropriate MST strategies, and the approach used in this study could potentially assist in the identification of faecal pollution sources.